2003
DOI: 10.1001/archotol.129.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Possible Impedance of Luminal Reepithelialization by Tracheal Cartilage Metalloproteinases

Abstract: Cartilage production and activity of MMP after injury to the large conducting airway may be a factor in the failure of luminal reepithelialization, resulting in aberrant repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…MMP2 and 9 are produced by cartilage from the trachea and bronchus, and cartilage conditioned medium decreases respiratory epithelial cell proliferation in vitro (Sigurdson et al, 2003). Addition of a broad, spectrum MMP inhibitor, GM6001, to this culture medium rescues epithelial cell proliferation suggesting that at least some of the MMPs produced by the cartilage repress respiratory cell proliferation (Sigurdson et al, 2003).…”
Section: Metalloproteinases In Epithelial Repairmentioning
confidence: 99%
“…MMP2 and 9 are produced by cartilage from the trachea and bronchus, and cartilage conditioned medium decreases respiratory epithelial cell proliferation in vitro (Sigurdson et al, 2003). Addition of a broad, spectrum MMP inhibitor, GM6001, to this culture medium rescues epithelial cell proliferation suggesting that at least some of the MMPs produced by the cartilage repress respiratory cell proliferation (Sigurdson et al, 2003).…”
Section: Metalloproteinases In Epithelial Repairmentioning
confidence: 99%
“…MMP-9 is the most prominently studied MMP in the lung and has been associated with a variety of lung diseases (4). The imbalance between MMP-9 and TIMP-1 is considered to contribute to the progression of airway remodeling in part due to changes in epithelial wound response (4,6,12,29,39,47,48).…”
mentioning
confidence: 99%
“…The involvement of MMPs, and particularly MMP-9, in airway wound repair and cell migration has already been reported in other studies (11,39). In contrast, it has been shown that MMP-2 and MMP-9 in conditioned medium from tracheal cartilage inhibit the adherence and proliferation of tracheal epithelial cells, an effect prevented by GM6001 (53).…”
Section: Discussionmentioning
confidence: 53%